Physicochemical and phytochemical analysis of three melon fruit (canary melon, watermelon, and muskmelon) peels, and their valorization in biscuits development - Hussain, Ashiq; Laaraj, Salah; Tikent, Aziz; Elfazazi, Kaoutar; Adil, Muhammad; Parveen, Saba; Bouhrim, Mohamed; Mothana, Ramzi A.; Noman, Omar M.; Eto, Bruno; Yaqub, Shazia; Fatima, Haya; et al. (Frontiers in Sustainable Food Systems, 2024)
Introduction Melons are highly sought after worldwide due to their exquisite and delectable taste. However, the peels of these fruits, which are rich in phytochemicals and sustainable components for innovative culinary formulations, are often discarded as waste. Methods This study explored the phytochemistry and valorization of three melon fruit, i.e., canary melon (Cucumis melo, var. Fonzy), watermelon (Citrullus lanatus, var. Augusta), and muskmelon (Cucumis melo, var. Cantaloupe), peels in food applications by incorporating into wheat flour biscuits. Peels of fruits were separated, dried and powders were extracted with 70% ethanol. Results and discussion Comparing the muskmelon fruit peel to the peels of the other two fruits, the muskmelon fruit peel had the significantly (p < 0.05) high ash (8.36%), fiber (12.06%), fat (1.21%), protein (5.02%), mineral contents (Mg 233, Ca 364, K 1605, Fe 49.72, and Zn 2.39 mg/100 g), total phenolic content (167.49 mg GAE/100 g), total flavonoid content (79.16 mg QE/100 g) and total antioxidant activity (56.92 mg Trolox equivalent/100 g). Results of the antimicrobial experiments of three melon peels showed that extracts from all peels showed enough antimicrobial activities, nearly comparable to the reference drugs (ampicillin and nystatin), which still showed the highest inhibition zones. Among three extracts, highest zone of inhibition against three bacterial species, i.e., Bacillus cereus (12.03 mm), Escherichia coli (10.02 mm), and Streptococcus aureus (18.08 mm), and fungal species, i.e., Candida albicans (8.09 mm), Aspergillus niger (7.06 mm), and Mucor meihi (7.02 mm) was exhibited by muskmelon peel extract. Moisture, ash, fat, fiber, minerals, phenolics, flavonoids, and antioxidant activities of biscuits were increased as a result of incorporating peel flours. Correlation showed TPC and TAA were highly correlated in watermelon (10%; 1). Using principal component analysis, adding 5% canary watermelon peel powder to biscuits improved their healthful and active elements while maintaining sensory features. Baking with 10% muskmelon or watermelon peel powder boosted nutrition and antioxidant activity. After the control, biscuits fortified with 5% melon peel powder exhibited significantly (p < 0.05) high sensory scores. These findings highlight the value of melon peels as sustainable ingredients, promoting waste reduction and enhancing the dietary and functional benefits of food products.